Case study: sleep and injury in elite soccer. A mixed method approach - Nédélec, M.; Leduc, C.; Dawson, B.; Guilhem, G.; Dupont, G. (The Journal of Strength and Conditioning Research, 2017)
The present case study allowed an examination of the link between sleep and injury occurrence in an elite male soccer player competing in French League 1 and Union of European Football Associations matches. During 4 months, a mixed method approach was used, combining actigraphic sleep assessment with qualitative interviews on a daily basis. Three injuries were reported over the study period. Sleep onset latency, both in the single night (117±43 min) and in the week (78±50 min) before injury occurrence, was longer than pre-season baseline values (18±13 min; effect size (ES): 3.1 and 1.6, respectively). Similarly, sleep efficiency in the single night (73±7%) and the week (75±7%) before injury occurrence, was lower than baseline (90±3%; ES: 3.2 and 2.8, respectively). In the present case-study, sleep onset latency and efficiency were altered on the night and in the week before injury occurrence. Individualized assessment of sleep during congested playing schedules may be useful to aid in preventing injury occurrence. Abstract from author